2017
DOI: 10.1038/ismej.2016.175
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of chemical gradients on microbial community structure

Abstract: Succession of redox processes is sometimes assumed to define a basic microbial community structure for ecosystems with oxygen gradients. In this paradigm, aerobic respiration, denitrification, fermentation and sulfate reduction proceed in a thermodynamically determined order, known as the ‘redox tower'. Here, we investigated whether redox sorting of microbial processes explains microbial community structure at low-oxygen concentrations. We subjected a diverse microbial community sampled from a coastal marine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 54 publications
3
63
0
Order By: Relevance
“…Community stability during the exposure to oxygen or nitrate was enabled by the increased expression of genes involved in oxidative and general stress protection. The stable coexistence of several fermenters and sulfate reducers with nitrate reducers or aerobic respirers supports the recent finding that microbial communities are assembled based on rules that go beyond those of the classical redox tower (Chen et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Community stability during the exposure to oxygen or nitrate was enabled by the increased expression of genes involved in oxidative and general stress protection. The stable coexistence of several fermenters and sulfate reducers with nitrate reducers or aerobic respirers supports the recent finding that microbial communities are assembled based on rules that go beyond those of the classical redox tower (Chen et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Our results were consistent with those reported by Chen et al . (), who found that unsorted redox processes, rather than a succession of redox processes, occurred in oxygen‐limited habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, much effort has gone into understanding microbial community structure in various environments involved in N 2 O emissions and responses to changes in environmental conditions, for example, O 2 depletion, higher temperature, lower pH, etc. (Fuchsman et al, ; Chen et al, ; Giles et al, ; Wu et al, ; Yin et al, ; Čuhel et al, ).…”
Section: Current and Future Methods For Assessing Sources And Sinks Omentioning
confidence: 99%